Incidence of Vibrio parahaemolyticus in Chesapeake Bay - Kaneko, Tatsuo (1975)
A Bay-wide survey of the distribution of Vibrio parahaemolyticus was carried out in Chesapeake Bay during May 1972, to determine whether the annual cycle of V. parahaemolyticus which was observed to occur in the Rhode River subestuary of Chesapeake Bay took place in other parts of Chesapeake Bay. In an earlier study, April to early June, when the water temperature rises from 14 to 19 C, was found to be a critical period in the annual cycle of the organism in the Rhode River, since this is the time period when the annual cycle is initiated. Results of this study, however, revealed that V. parahaemolyticus could not be found in the water column during May 1972. Neverthless, several samples of sediment and plankton yielded V. parahaemolyticus isolates. Comparison of data with those for the Rhode River area examined in the earlier studies of the annual cycle of V. parahaemolyticus suggests that the time of initiation of the annual cycle of V. parahaemolyticus in the open Bay proper may be influenced by various factors such as temperature and salinity, i.e., deeper water locations may show initiation of the V. parahaemolyticus annual cycle later than shallow areas. Confirmation of the presence of the organism in the samples studied was accomplished using numerical taxonomy with 19 reference strains also included in the analyses.